Coupled cycling programs multicellular self-organization of neural progenitors. Issue 17 (2nd September 2019) - Rezaei-Lotfi, Saba; Hunter, Neil; Farahani, Ramin M
ABSTRACT: Self-organization is central to the morphogenesis of multicellular organisms. However, the molecular platform that coordinates the robust emergence of complex morphological patterns from local interactions between cells remains unresolved. Here we demonstrate that neural self- organization is driven by coupled cycling of progenitor cells. In a coupled cycling mode, intercellular contacts relay extrinsic cues to override the intrinsic cycling rhythm of an individual cell and synchronize the population. The stringency of coupling and hence the synchronicity of the population is programmed by recruitment of a key coupler, β-catenin, into junctional complexes. As such, multicellular self-organization is driven by the same basic mathematical principle that governs synchronized behavior of macro-scale biological systems as diverse as the synchronized chirping of crickets, flashing of fireflies and schooling of fish; that is synchronization by coupling. It is proposed that coupled cycling foreshadows a fundamental adaptive change that facilitated evolution and diversification of multicellular life forms.